Low Dose Oral Vitamin K to Reverse Acenocoumarol-induced Coagulopathy: A Randomized Controlled Trial - Ageno, W.; Crowther, M.; Steidl, L.; Ultori, C.; Mera, V.; Dentali, F.; Squizzato, A.; Marchesi, C.; Venco, A. (Thrombosis and Haemostasis, 2002)
Low dose oral vitamin K rapidly reverses warfarin-associated coagulopathy. Its effect in patients receiving acenocoumarol is uncertain. We compared the effect of withholding acenocoumarol and administering 1 mg oral vitamin K with simply withholding acenocoumarol in asymptomatic patients presenting with INR values between 4.5 and 10.0. The primary end-point of the study was the INR value on the day following randomisation. We found that patients receiving oral vitamin K had more sub-therapeutic INR levels than controls (36.6% and 13.3%, respectively; RR 1.83, 95% confidence interval 1.16, 2.89) and a lower, but non-significant, proportion of INR values in range (50% and 66.6%, respectively) on the day following randomisation. After 5 ± 1 days, there were more patients with an INR value in range in the vitamin K group than in controls (74.1% and 44.8%, respectively). There were no clinical events during 1 month follow-up. We conclude that the omission of a single dose of acenocoumarol is associated with an effective reduction of the INR in asymptomatic patients presenting with an INR value of 4.5 to 10.0. Furthermore, the use of a 1 mg dose of oral vitamin K results in an excessive risk of overreversal of the INR.
Keywords: Oral vitamin K; acenocoumarol; oral anticoagulants